IL-37- and IL-35/IL-37-Producing Plasma Cells in Chronic Periodontitis. (July 2019) - Jing, L.; Kim, S.; Sun, L.; Wang, L.; Mildner, E.; Divaris, K.; Jiao, Y.; Offenbacher, S.
Periodontitis is one of the most prevalent chronic inflammatory diseases and is induced by the interaction between oral microorganisms and the host immune system. Plasma cells are of special interest in chronic periodontitis (CP), as they represent 50% of infiltrated immune cells in periodontal lesions. Plasma cells constitute the only known cell type capable of antibody production; however, recent evidence supports an emerging role for distinct sets of plasma cells in cytokine production. However, the presence of cytokine-producing plasma cells in CP is unknown. In this study, we used immunohistochemistry to detect significantly elevated levels of IL-35 and IL-37 (2 recently identified anti-inflammatory cytokines) in CP gingival tissue as compared with healthy tissue. Remarkably, we demonstrate that CD138 + CD38 + plasma cells are the major immune cell type in CP gingival tissues and that these cells produce IL-35 and IL-37. We used immunofluorescence and confocal microscopy analysis to identify a subset of plasma cells with robust cytoplasmic expression of IL-37—we denote this subset as IL-37-producing plasma cells (CD138 + CD38 + PIL-37 ). Another subset of plasma cells coproduces IL-35 and IL-37 and is denoted as IL-37/IL-35-coproducing plasma cells (CD138 + CD38 + PIL-35/IL-37 ). We determined that these 2 plasma cell subsets are IgG + plasma cells. Moreover, we show that human recombinant IL-35 and IL-37 exhibit a dose-dependent inhibition of osteoclast formation in vitro ( 78.9% and 97.7% inhibition in 300 ng/mL of IL-35 and IL-37, respectively, P < 0.05). Overall, our findings suggest that PIL-37 and PIL-35/IL-37 exist as subsets of plasma cells in CP lesions and that these 2 new types of plasma cells may regulate periodontitis pathogenesis by inhibiting alveolar bone loss through directly blocking osteoclast formation. Importantly, these data suggest a novel role of plasma cells and offer potential new mechanistic and regulatory targets to be investigated in the context of periodontal health and disease.